Culture And Human Development: City Dynamics And Its Historical Heritage In Akure (2006)
Culture has to do with the beliefs of the people, which may be tangible or intangible. Culture and human development are actively related. Technological development viewed from a broad perspective may be development from above or development from below. The development from above has its roots in the neo-classical economic theory. The development from below on the other hand, focuses on the maximum mobilization of the natural, human and institutional resources, with the primary objective being the satisfaction of the basic need of the inhabitants under review. This paper critically examines the historical antecedent of some Yoruba communities in respect of their cultural identities, heritages and monuments, using Akure as a case study. This will help to fathom the rate of changes that had occurred from the past 50 years, in order to elicit vital lessons useful for the present